Hydrogen Peroxide, Signaling in Disguise during Metal Phytotoxicity - Cuypers, Ann; Hendrix, Sophie; Amaral dos Reis, Rafaela; De Smet, Stefanie; Deckers, Jana; Gielen, Heidi; Jozefczak, Marijke; Loix, Christophe; Vercampt, Hanne; Vangronsveld, Jaco; Keunen, Els (Frontiers in Plant Science, 2016)
Plants exposed to excess metals are challenged by an increased generation of reactive oxygen species (ROS) such as superoxide (O2•-), hydrogen peroxide (H2O2) and the hydroxyl radical (•OH). The mechanisms underlying this oxidative challenge are often dependent on metal-specific properties and might play a role in stress perception, signaling and acclimation. Although ROS were initially considered as toxic compounds causing damage to various cellular structures, their role as signaling molecules became a topic of intense research over the last decade. Hydrogen peroxide in particular is important in signaling because of its relatively low toxicity, long lifespan and its ability to cross cellular membranes. The delicate balance between its production and scavenging by a plethora of enzymatic and metabolic antioxidants is crucial in the onset of diverse signaling cascades that finally lead to plant acclimation to metal stress. In this review, our current knowledge on the dual role of ROS in metal-exposed plants is presented. Evidence for a relationship between H2O2 and plant metal tolerance is provided. Furthermore, emphasis is put on recent advances in understanding cellular damage and downstream signaling responses as a result of metal-induced H2O2 production. Finally, special attention is paid to the interaction between H2O2 and other signaling components such as transcription factors, mitogen-activated protein kinases, phytohormones and regulating systems (e.g. microRNAs). These responses potentially underlie metal-induced senescence in plants. Elucidating the signaling network activated during metal stress is a pivotal step to make progress in applied technologies like phytoremediation of polluted soils.